RANCANG SISTEM PENDUKUNG KEPUTUSAN UNTUK KELAYAKAN PENERIMA BANTUAN SOSIAL TUNAI (BST) PADA MASYARAKAT MISKIN BERBASIS WEBSITE MENGGUNAKAN METODE FUZZY (FMADM) ARAS (STUDI KASUS : KELURAHAN PORIS PLAWAD INDAH, KECAMATAN CIPONDOH) - Dahlan Supriatna; Agung Perdananto (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Poris Plawad Indah Sub-District is an institution whose duties include collecting community data to determine the eligibility of the recipient community of cash social assistance (BST). Therefore, in its implementation, Poris Plawad Indah Village has a program to select the eligibility of recipients of social assistance (BST). In conducting community eligibility elections, this agency has not used a system that makes it easy for the election committee to determine who is a suitable candidate. As a result, the election runs ineffectively because the time used is very long. The DSS system for selecting community feasibility uses the Fuzzy ARAS method with the waterfall system development method which aims to get an overview of the system that is in accordance with what is needed in Poris Plawad Indah Village. Therefore, with the DSS website system, selecting community eligibility, the community eligibility selection committee in Poris Plawad Indah Village will be greatly facilitated.